GalNAc-T13 maintains neurite architecture and memory retention via O-GalNAc glycosylation of seizure protein 6 - Yao Deng; Xia Zou; Han Zhang; Xiaoyan Lu; Xingming Zhao; Wenjuan Jia; Yingjiao Xu; Fang Yang; Hisashi Narimatsu; Yan Zhang (Proceedings of the National Academy of Sciences, 2026)
Glycosylation, a key and prevalent modification in brain proteins and lipids, is essential for brain development and function. O-GalNAc glycosylation, initiated by the family of polypeptide N-acetylgalactosaminyltransferases (GalNAc-Ts, GALNT s), is the most abundant type of O-glycosylation in the brain. Despite growing evidence linking GALNT variations to neuropsychiatric disorders, the molecular roles and underlying mechanisms by which O-GalNAc glycosylation contributes to brain functions remain poorly characterized. Here, we focus on GalNAc-T13, a member of the GalNAc-T family that is highly expressed in the brain. We established a brain-specific Galnt13 conditional knockout mouse model and found that these mice exhibited reduced neurite length, simplified dendritic branching, and decreased dendritic spine density in the cerebral cortex across embryonic and adult stages. Behavioral analyses further revealed impaired spatial memory consolidation following Galnt13 knockout. Mechanistically, we identified seizure protein 6 (SEZ6), a neurodevelopment-related protein, as a key substrate of GalNAc-T13 using a lectin-based mass spectrometry glycoproteomic approach. Our results demonstrated that GalNAc-T13 regulates the O-GalNAc glycosylation levels of SEZ6 with high catalytic efficiency in vitro and in vivo, improving protein stability and its interaction with PRSS12 at the cell surface to promote neurite outgrowth. Collectively, these findings suggest a critical role for GalNAc-T13 in maintaining cortical neurite architecture and memory retention, providing a mechanistic example for understanding the function of O-GalNAc glycosylation in the brain.